2022
DOI: 10.3390/ijerph192013043
|View full text |Cite
|
Sign up to set email alerts
|

Co-Creation and Co-Production of Health Promoting Activities Addressing Older People—A Scoping Review

Abstract: The global population is aging and the promotion of health and well-being for this generation is essential. Co-creative and co-productive practices can be solutions to welfare challenges in local policies. Therefore, this scoping review aimed to understand the extent and type of evidence in relation to the co-creation and co-production of health-promoting activities addressing older people aged 60+ years and to examine the influence of co-creative and co-productive activities on health and well-being, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Age and dementia-friendly processes were a common focus, including clinical partnerships [57 ▪▪ ,58 ▪▪ ,59,60 ▪ ], caregiving support and patient navigation [61 ▪ ,62 ▪ ]. They included ethical, financial, and infrastructural aspects of care [63 ▪▪ ,64 ▪ ,65 ▪▪ ,66 ▪▪ ,67,68].…”
Section: Resultsmentioning
confidence: 99%
“…Age and dementia-friendly processes were a common focus, including clinical partnerships [57 ▪▪ ,58 ▪▪ ,59,60 ▪ ], caregiving support and patient navigation [61 ▪ ,62 ▪ ]. They included ethical, financial, and infrastructural aspects of care [63 ▪▪ ,64 ▪ ,65 ▪▪ ,66 ▪▪ ,67,68].…”
Section: Resultsmentioning
confidence: 99%
“…We use the term equity‐deserving groups (EDGs) to refer to populations of varying sociohistoric, political, economic and cultural contexts, both locally and globally, who are and have been more likely to experience systemic oppression via population‐level barriers to health and well‐being and limitations in access to services (e.g., groups that include Black, Indigenous, racialized, disabled, 2SLGBTQI+ people). Cocreation has been used with diverse populations to develop a range of health and social services and tools, for example, mental health services with youth, 12 research training tools with youth with disabilities and caregivers, 13 transit systems with older newcomers, 14 and health promotion activities with older adults 15 . A common element in these diverse projects is the inclusion of people with lived and living experience.…”
Section: Introductionmentioning
confidence: 99%
“…Cocreation has been used with diverse populations to develop a range of health and social services and tools, for example, mental health services with youth, 12 research training tools with youth with disabilities and caregivers, 13 transit systems with older newcomers, 14 and health promotion activities with older adults. 15 A common element in these diverse projects is the inclusion of people with lived and living experience. The language for people who develop expertise through their own experience (e.g., with a health condition or use of a service) has been debated, 16 , 17 , 18 however we have used the term experience expert (EE) to recognise the valuable insights and valid embodied knowledge(s) rooted in body consciousness that people have and may share if provided with opportunities to do so.…”
Section: Introductionmentioning
confidence: 99%
“…According to research in private services industry (Bordian et al, 2023;Gonz alez-Mansilla et al, 2019;Prebensen and Xie, 2017), customers are more satisfied when they participate in value cocreation activities. Customers of public services, such as healthcare (Fusco et al, 2023;Terkelsen et al, 2022), local government (Bentzen, 2022;Larsen and Caswell, 2022) and higher education (Bovill, 2020;Cavallone et al, 2021;Goi et al, 2022), have also been found to be more satisfied as a result of engaging in value co-creation behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…, 2019; Prebensen and Xie, 2017), customers are more satisfied when they participate in value co-creation activities. Customers of public services, such as healthcare (Fusco et al ., 2023; Terkelsen et al. , 2022), local government (Bentzen, 2022; Larsen and Caswell, 2022) and higher education (Bovill, 2020; Cavallone et al.…”
Section: Introductionmentioning
confidence: 99%